Two new species and a new record of Gelechiidae (Lepidoptera) from Korea - Ponomarenko, Margarita; Park, Kyu-Tek (Zootaxa, 2007)
Two new species of Gelechiidae, Teleiopsis motleella, sp. nov., and Sitotroga pseudopsacasta, sp. nov., are described from Korea. Illustrations of adults and male genitalia are provided. Scrobipalpa spumata (Povolný, 2001), comb. n., is newly recorded from Korea. It was described from the female, and the male genitalia are described and illustrated for the first time.